Sex- and Age-Related Physiological Profiles for Brachial, Vertebral, Carotid, and Femoral Arteries Blood Flow Velocity Parameters During Growth and Aging (4–76 Years): Comparison With Clinical Cut-Off Levels - Zócalo, Yanina; Bia, Daniel (Frontiers in Physiology, 2021)
Ultrasound-derived blood flow velocity (BFV) levels (e.g., peak systolic velocity, PSV), intra-beat indexes (e.g., resistive) and inter-segment ratios (e.g., internal/common carotid artery (ICA/CCA) PSV ratio) are assessed to describe cardiovascular physiology and health status (e.g., disease severity evaluation and/or risk stratification). In this respect, fixed cut-off values (disregard of age or sex) have been proposed to define `significant´ vascular disease from BFV-derived data (parameters). However, the use of single fixed cut-off values has limitations. An accurate use of BFV-derived parameters requires knowing their physiological age-related profiles and the expected values for a specific subject. To our knowledge there are no works that have characterized BFV profiles in large populations taking into account: (i) data from different age-stages (as a continuous) and transitions (childhood-adolescence-adulthood), (ii) complementary parameters, (iii) data from different arteries, and (iv) potential sex- and hemibody-related differences. Furthermore, (v) there is little information regarding normative data (reference intervals (RIs)) for BFV indexes. Aims: (a) To determine the need for age-, body side- and sex-specific profiles for BFV levels and derived parameters (intra-beat indexes and inter-segment ratios), and (b) to define RIs for BFV levels and parameters, obtained from CCA, ICA, external carotid, vertebral, femoral and brachial arteries records. Methods: 3619 subjects (3-90 years) were included; 1152 were healthy (without cardiovascular disease and atheroma plaques) and non-exposed to cardiovascular risk factors. BFV data were acquired. The agreement between left and right data was analyzed (Concordance correlation, Bland-Altman). Mean and standard deviation equations and age-related profiles were obtained for BFV levels and parameters (regression methods; fractional polynomials). Results: Left and right body-side derived data were not always equivalent. The need for sex-specific RIs was dependent on the parameter and/or age considered. RIs were defined for each studied artery and parameter. Percentile curves were compared with recommended fixed cut-off points. The equations for sex, body-side and age-specific BFV physiological profiles obtained in the large population (of children, adolescents and adults) studied were included (spreadsheet formats), enabling to determine, for a particular subject, the expected values and potential data-deviations.